Molecular Basis of the Chemiluminescence Mechanism of Luminol. Issue 20 (15th March 2019) - Giussani, Angelo; Farahani, Pooria; Martínez‐Muñoz, Daniel; Lundberg, Marcus; Lindh, Roland; Roca‐Sanjuán, Daniel
Abstract: Light emission from luminol is probably one of the most popular chemiluminescence reactions due to its use in forensic science, and has recently displayed promising applications for the treatment of cancer in deep tissues. The mechanism is, however, very complex and distinct possibilities have been proposed. By efficiently combining DFT and CASPT2 methodologies, the chemiluminescence mechanism has been studied in three steps: 1) luminol oxygenation to generate the chemiluminophore, 2) a chemiexcitation step, and 3) generation of the light emitter. The findings demonstrate that the luminol double‐deprotonated dianion activates molecular oxygen, diazaquinone is not formed, and the chemiluminophore is formed through the concerted addition of oxygen and concerted elimination of nitrogen. The peroxide bond, in comparison to other isoelectronic chemical functionalities (−NH−NH−, −N − −N − −, and −S−S−), is found to have the best chemiexcitation efficiency, which allows the oxygenation requirement to be rationalized and establishes general design principles for the chemiluminescence efficiency. Electron transfer from the aniline ring to the OO bond promotes the excitation process to create an excited state that is not the chemiluminescent species. To produce the light emitter, proton transfer between the amino and carbonyl groups must occur; this requires highly localized vibrational energy during chemiexcitation. Abstract : Luminol chemiluminescence : Light emission from luminol is a popular chemiluminescence reaction. However, the mechanism is complex and different possibilities have been proposed. By efficiently combining DFT and CASPT2 methodologies, the chemiluminescence mechanism of luminol has been elucidated.